Autism Awareness On Tiktok: Impact On Youth Perceptions - Nur Danisa Humaira A Dzulkifli; Madihah Humaira Masharudean; Aisya Humayrah Mohd Ihsan; Nur Ifatul Izzara Mahamad; Mohamad Hafifi Jamri; Ferry Kurnia Rizkiyansyah (Public Knowledge, 2024)
Autism spectrum disorders (ASD) comprise a wide range of conditions characterised by varying degrees of challenges with social interaction and communication. Meanwhile, TikTok is a social media platform that allows users to share short videos. The purpose of this study is to measure the level of youth’s awareness towards autism spectrum disorder (ASD) on TikTok and to reduce stigma towards autism spectrum disorder (ASD) among youth. The study adopted magic bullet theory as the basis for developing its model. A total of 408 respondents, comprising multi-ethnic Malaysian youth between the ages of 15-40 who have exposure to social media usage, participated through an online questionnaire distributed to them. Both convenience sampling and purposive sampling were integrated for data collection. Manual analysis was done to analyze the collected research data. The main findings of the study showed that exposure to autism awareness content on TikTok has emerged as a powerful catalyst in transforming youths’ attitudes toward autism. Overall, this study revealed that TikTok could be used as an effective tool to spread awareness and change the stigma or negative perception of youth towards ASD issues.